Constructing Ecological Networks and Analyzing Impact Factors in Multi-Scenario Simulation Under Climate Change - Hua Bai; Yaoyun Zhang; Jiazhuo Huang; Haopeng Chen (Land)
Persistent climate change and anthropogenic activities have caused the degradation of urban ecosystems and the fragmentation of landscapes in the Loess Plateau region, situated in northern China. Ecological networks have been considered an effective measure for reducing urban habitat fragmentation, enhancing landscape connectivity, and identifying priority areas for ecological restoration. However, research on the spatiotemporal dynamics of ecological networks in cities in the Loess Plateau region, especially multi-scenario ecological networks under future climate change scenarios, and the drivers affecting these network elements are still limited. This study analyzed the spatiotemporal dynamic changes in the ecological networks in Shenmu City from 2000 to 2035, and used GeoDetector to explore the driving factors influencing changes in ecological source distribution. The results showed the following: (1) The ecological sources in Shenmu City continued to shrink from 2000 to 2020, while landscape fragmentation increased. By 2035, the results of scenario modeling will differ for different Shared Socioeconomic Pathways (SSPs) and Representative Concentration Pathways (RCPs), with the ecological source area increasing under scenarios SSP119 and SSP245, and continuing to decrease under scenario SSP585. (2) From 2000 to 2020, the α, β, and γ indices increased and then declined, while the ecological networks of the SSP119 and SSP585 scenarios will stabilize. (3) Under the optimal scenario SSP119, 27 ecological pinch points and 40 ecological barrier points will be identified, which are priority areas for the future execution of ecological restoration initiatives. (4) Precipitation is the primary factor that affects the distribution of ecological sources, followed by temperature. This study proposes a new research perspective on ecological networks, and provides a guideline for ecological restoration and conservation in cities (counties) in the Loess Plateau region.